Optimizing the Pesantren Environment to Enhance Speaking Skills: A Case Study - Putri, Faradila Arsylia; Pranata, Mohammad Sofyan Adi (Journal of English Language and Education, 2025)
This study explores how the learning environment at Nurul Jadid Islamic Boarding School can be better leveraged to help students improve their English speaking skills. Through a qualitative case study, the researcher gathered insights from five eighth-semester English Education students using interviews, observations, and document analysis. The findings reveal that structured language programs, peer collaboration, supportive teacher role models, and the use of English in religious activities all play a meaningful role in expanding students’ vocabulary, boosting their confidence, and sharpening their grammar awareness. Despite these positive factors, several challenges remain such as inconsistent enforcement of language rules, limited interaction with fluent or native speakers, and students’ anxiety about making mistakes when speaking. To make the most of the professional environment, the study highlights the need for stronger institutional backing, more engaged teachers, and increased opportunities for authentic speaking practice. Overall, the research shows that Islamic boarding schools hold strong potential as effective spaces for language development, especially within religious education contexts.